2022
DOI: 10.3390/v14040802
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of COVID-19 Vaccine Breakthrough Infections: A Prospective Cohort Study in Belgium

Abstract: The objective of this study was to investigate the incidence and risk factors associated with COVID-19 vaccine breakthrough infections. We included all persons ≥18 years that had been fully vaccinated against COVID-19 for ≥14 days, between 1 February 2021 and 5 December 2021, in Belgium. The incidence of breakthrough infections (laboratory confirmed SARS-CoV-2-infections) was determined. Factors associated with breakthrough infections were analyzed using COX proportional hazard models. Among 8,062,600 fully va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
27
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 32 publications
11
27
3
Order By: Relevance
“…Moreover, although individuals receiving AZD1222 vaccine (versus BNT162b2 [Pfizer BioNTech]) were more likely to have lower antibody levels after first and second vaccination, these differences were no longer evident after third vaccination. Our finding is also consistent with lower vaccine effectiveness estimates and increased post-vaccination infection incidence after first or second vaccination following AZD1222 versus BNT162b2 [15,42,43], but only minor differences after third vaccination [15,44].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, although individuals receiving AZD1222 vaccine (versus BNT162b2 [Pfizer BioNTech]) were more likely to have lower antibody levels after first and second vaccination, these differences were no longer evident after third vaccination. Our finding is also consistent with lower vaccine effectiveness estimates and increased post-vaccination infection incidence after first or second vaccination following AZD1222 versus BNT162b2 [15,42,43], but only minor differences after third vaccination [15,44].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, Stouten et al noted a BTI incidence of 4.6% (n = 373,070/8,0620,600) in fully vaccinated individuals in Belgium. The researchers calculated a 11 per 100 person years risk to develop a BTI after BNT162b2-based vaccination, which was lower than subjects vaccinated with adeno-vector-based vaccines but higher than those who received the mRNA-1273 vaccine [76]. Moreover, a report evaluating BTI occurrence in the capital region of Denmark (n = 1,088,879) mentioned an overall low incidence (hazard ratio of 0.2%) with a tendency towards higher risk to develop BTI with longer time post-vaccination [77].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to other research the menace of BT infection was lower amongst previously infected people. 4 , 33 Stamatatos et al reported that previously infected COVID‐19 patients will benefit from immunization as it will significantly increase neutralizing antibody responses against vaccine‐matched and emerging variants. However, little research showed that prior infection in vaccinated people did not significantly reduce the risk of BT infection.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 As the COVID‐19 vaccine manufacturer companies started to be administered globally, the despondency consequences of COVID‐19 were mitigated. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation